Question
upstudy study bank question image url

Question 6 of 10 Solve the system of equations below. \[ \begin{aligned} 4 x+y=16 \\ 2 x+3 y=-2\end{aligned} \] \[ \begin{array}{l}\text { A. }(5,-4) \\ \text { B. }(4,-5) \\ \text { c. }(5,4) \\ \text { D. }(-5,4)\end{array} \]

Ask by Delgado Wang. in the United States
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solution to the system is (5, -4), which is option A.

Solution

We start with the system:   4x + y = 16    (1)   2x + 3y = -2   (2) Step 1: Solve equation (1) for y.   y = 16 - 4x Step 2: Substitute y = 16 - 4x into equation (2):   2x + 3(16 - 4x) = -2 Step 3: Expand and simplify:   2x + 48 - 12x = -2   -10x + 48 = -2 Step 4: Isolate x:   -10x = -2 - 48   -10x = -50   x = (-50)/(-10) = 5 Step 5: Substitute x = 5 back into y = 16 - 4x:   y = 16 - 4(5) = 16 - 20 = -4 Thus, the solution to the system is (5, -4). The correct answer is A.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To solve the system of equations, we will use substitution or elimination. Let's start by solving for \(y\) from the first equation: \[ y = 16 - 4x \] Now we can substitute this expression for \(y\) into the second equation: \[ 2x + 3(16 - 4x) = -2 \] Distributing the 3 gives: \[ 2x + 48 - 12x = -2 \] Combining like terms: \[ -10x + 48 = -2 \] Next, we'll isolate \(x\): \[ -10x = -2 - 48 \] \[ -10x = -50 \] \[ x = 5 \] Now that we have \(x\), we can substitute it back into the first equation to find \(y\): \[ 4(5) + y = 16 \] \[ 20 + y = 16 \] \[ y = 16 - 20 \] \[ y = -4 \] Thus, the solution to the system of equations is \((5, -4)\), which corresponds to option A.

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy